Syntactic Means of Forming the Image of a Politician in Headlines of Leading American Newspapers - Yu. V. Shuyskaya; R. Yu. Anisimov; E. A. Drozdova (Научный диалог)
Syntactic means of forming the image of a politician in the headlines of English-language newspapers on the material of the websites of the corresponding publications are considered in the article. The relevance of the study is due to the fact that in 2020—2021 online media acquired particular importance: in the conditions of isolation associated with the pandemic, many readers, instead of the printed version of the newspaper, began to read the online version, the design of which allows you to read the headline and lead without seeing the main text of the titled material. The question is raised about the order of words and the position of the leader’s sur-name in the sentence as a means of positioning the figure of a political leader. The results of a comparative analysis of the headlines of “The New York Times” and “The Washington Post” for the period January 20, 2009 — February 20, 2009, Jan-uary 20, 2017 — February 20, 2017, January 20, 2021 — February 20, 2021 are presented. These periods correspond to the first month in office of US President Barack Obama (2009], Donald Trump (2017) and Joseph Biden (2021]. It has been proven that news-papers use manipulative technologies in headlines, relying on the communicative role of the subject and its place in the structure of the sentence. In particular, the president supported by this media is positioned as an active politician and the main character, while the unsupported president is positioned as a secondary and inactive one.